LITERASI DIGITAL MAHASISWA BKPI FITK UIN SUMATERA UTARA MEDAN TAHUN 2021 - Ali Daud Hasibuan (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2021)
This study describes the digital literacy of students BKPI FITK State Islamic University of North Sumatera Utara (UIN-SU) in Medan. Quantitative descriptive method was used in doing this study. There were 191 students BKPI FITK UIN-SU Medan in 2021 being samples for this study. The instrument of this study was questionnaire using a five-likert scales. Data obtaining process was conducted by utilizing google form which was shared to students. The results of study revealed that students’ digital literacy score is 70 which means average. The highest aspect of students’ digital literacy is safety aspect which shows score 20.68 and the lowest one is skill aspect namely 15.36. Based on sex type, female-students’ digital literacy is higher than male-students. Female-students’ digital literacy score is 73.19, meanwhile male-students is just 71.48. Moreover, digital literacy of students graduated from public senior high school is higher than students graduated from Islamic boarding school or pesantren. Specifically, the score of the former is 75.14 and the latter is 69.50.